2005
DOI: 10.1103/physrevb.72.085402
|View full text |Cite
|
Sign up to set email alerts
|

Indirect exchange coupling between magnetic adatoms in carbon nanotubes

Abstract: The long-range character of the exchange coupling between localized magnetic moments indirectly mediated by the conduction electrons of metallic hosts can play a significant role in determining the magnetic order of low-dimensional structures. Here we consider how this indirect coupling influences the magnetic alignment of adatoms attached to the walls of carbon nanotubes. A general expression for the indirect coupling in terms of single-particle Green functions is presented. Contrary to the general property t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
71
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 14 publications
6
71
0
Order By: Relevance
“…A monotonic form is found for the black line representing V g = 0, due to the familiar commensurability effect that exists in half-filled electronic bands in hexagonal atomic structures. [27][28][29][30] As a matter of fact, for the same reason, this monotonicity is also found everywhere outside the gated region. As the gate voltage is increased to V g = ⌬ and V g =2⌬ we depart from a commensurate regime and enter a region where clear oscillatory patterns are seen.…”
mentioning
confidence: 91%
“…A monotonic form is found for the black line representing V g = 0, due to the familiar commensurability effect that exists in half-filled electronic bands in hexagonal atomic structures. [27][28][29][30] As a matter of fact, for the same reason, this monotonicity is also found everywhere outside the gated region. As the gate voltage is increased to V g = ⌬ and V g =2⌬ we depart from a commensurate regime and enter a region where clear oscillatory patterns are seen.…”
mentioning
confidence: 91%
“…Earlier calculations have suggested that the existence of this current is sufficient to induce a dynamic magnetic coupling between dispersed impurities in NT, which is far more pronounced and long ranged than any other magnetic coupling of static nature. 7,8,14,15 To test how this precession propagates, in Fig. 2 we show ͉͗S m ͑t͉͒͘ probed at different locations on the NT.…”
Section: ͑1͒mentioning
confidence: 99%
“…For a pristine NT g mj ͑ ͒ may be analytically determined 14 and the integration in Eq. ͑1͒ performed with great numerical accuracy.…”
Section: ͑1͒mentioning
confidence: 99%
“…We will call the energies of the acoustic and optical mode as ⍀ 0 and ⍀ 1 , respectively. The existence of a frequency splitting between the two modes means that there is a static Ruderman-KittelKasuya-Yoshida ͑RKKY͒-type exchange coupling between m ជ A and m ជ B , 12 which is proportional to the splitting. The solid curve displays a measure of the dynamical coupling, −Im BA ͑⍀͒; its absolute value is proportional to the amplitude of the magnetization precession induced on B by a transverse circularly polarized field applied on A.…”
mentioning
confidence: 99%
“…The splitting is proportional to the static exchange coupling between m ជ A and m ជ B , which is known to oscillate as a function of N. [12][13][14] The static coupling decays, for quasi-one-dimensional systems, asymptotically as 1 / N; hence oscillations in the dynamic coupling should be seen even for relatively large values of N.…”
mentioning
confidence: 99%